Small-molecule correctors of defective ΔF508-CFTR cellular processing identified by high-throughput screening - Pedemonte, Nicoletta (American Society for Clinical Investigation, 2005)
The most common cause of cystic fibrosis (CF) is deletion of phenylalanine 508 (ΔF508) in the CF transmembrane conductance regulator (CFTR) chloride channel. The ΔF508 mutation produces defects in folding, stability, and channel gating. To identify small-molecule correctors of defective cellular processing, we assayed iodide flux in ΔF508-CFTR–transfected epithelial cells using a fluorescent halide indicator. Screening of 150,000 chemically diverse compounds and more than 1,500 analogs of active compounds yielded several classes of ΔF508-CFTR correctors (aminoarylthiazoles, quinazolinylaminopyrimidinones, and bisaminomethylbithiazoles) with micromolar potency that produced greater apical membrane chloride current than did low-temperature rescue. Correction was seen within 3–6 hours and persisted for more than 12 hours after washout. Functional correction was correlated with plasma membrane expression of complex-glycosylated ΔF508-CFTR protein. Biochemical studies suggested a mechanism of action involving improved ΔF508-CFTR folding at the ER and stability at the cell surface. The bisaminomethylbithiazoles corrected ΔF508-CFTR in ΔF508/ΔF508 human bronchial epithelia but did not correct a different temperature-sensitive CFTR mutant (P574H-CFTR) or a dopamine receptor mutant. Small-molecule correctors may be useful in the treatment of CF caused by the ΔF508 mutation.